DAMPAK PERUBAHAN STATUS SOSIAL TERHADAP UPACARA RAMBU SOLOâ€™ DI KELURAHAN TONDON MAMULLU KECAMATAN MAKALE KABUPATEN TANA TORAJA - Patadungan, Ellyn; Purwanto, A.; Waani, Fonny J. (HOLISTIK, Journal Of Social and Culture, 2020)
Rambu Soloâ€™ is a traditional ceremony of the death of the Toraja people who aims to respect and deliver the spirits of the deceased to the spirit realm. At first the festive party was only carried out by the nobility, but now it has begun to shift, who is rich is what the party is festive. This study is entitled â€The Impact of Changes Social status towards Rambu Solo ceremony in Tondon Mamullu Village, Makale District, Tana Toraja District", with the problem formulation of how the implementation of the Rambu Solo Ceremony based on customary rules and how influence of changes Social Status to the Rambu Solo Ceremony' in Tondon Mamullu village, Makale District, Tana Toraja District. The purpose of this study is to researching more deeply the implementation of the Rambu Solo Ceremony based on customary rules and how influence of changes Social Status to the Rambu Solo Ceremony' in Tondon Mamullu village, Makale District, Tana Toraja District. Based on the research results obtained that the implementation of the Rambu Solo Ceremony 'the Toraja community not working run as it should and has experienced changes or shifted in the implementation. The implementation of the Rambu Soloâ€™ ceremonythe Toraja public, specifically the community of Tondon Mamullu Village has been background by several things, namely Economic Status, Education, Employment, Self-Esteem / Prestige, and Prestige / Pride. Rambu Soloâ€™ which is implemented by the Toraja people at this time is not too traditional and has an impact on the traditional values of Rambu Solo' which has actually started to disappear and the values that are applied today are contemporary. Keyword: Rambu Soloâ€™, Social Status, Impact